Risk of Colorectal Cancer in Patients With Attention-Deficit Hyperactivity Disorder: A Nationwide, Population-Based Cohort Study - Hu, Je-Ming; Lee, Chia-Cheng; Lin, Tzu-Chiao; Chung, Chi-Hsiang; Chen, Chao-Yang; Chang, Pi-Kai; Hsiao, Cheng-Wen; Sun, Chien-An; Tzeng, Nian-Sheng; Chien, Wu-Chien (Frontiers in Psychiatry, 2021)
ABSTRACT Background: The association between attention-deficit hypersensitivity disorder (ADHD) and the risk of developing colorectal cancer (CRC) is, as yet, to be investigated, and thus, we have conducted this nationwide, cohort study to examine the association in patients from Taiwan. Methods: In this study, 798 individuals with newly diagnosed ADHD and 2,394 (1:3) age-, gender-, and index year- matched controls without ADHD were enrolled, between 2000 and 2013, from the Longitudinal Health Insurance Database, a subset of the National Health Insurance Research Database in Taiwan. The cumulative incidence of CRC was assessed in each cohort by the Kaplan–Meier method. The multivariate Cox proportional hazards model was used to estimate the crude, and the adjusted hazards ratios (HRs) with 95% confidence intervals (CIs), was conducted to estimate the association between ADHD and CRC. Results: The Kaplan–Meier analysis revealed that the cumulative incidence of CRC was significantly higher in patients with ADHD than in those without it (log rank test, p < 0.001). After adjustments for age, gender, comorbidities, and other covariates, the ADHD group was associated with an increased risk of CRC in comparison to the non-ADHD group (adjusted HR = 3.458, 95% CI = 1.640–7.293, p < 0.001). In addition, the usage of methylphenidate was not associated with the risk of developing CRC in patients with ADHD. Conclusion: This retrospective cohort study depicts the evidence that ADHD was associated with the increased risk of CRC. Further studies are needed to confirm the association and the underlying mechanisms.